OCCURRENCE OF THE LATE-SERPUKHOVIAN BIOGERMS IN THE NORTH-EASTERN PART OF THE DON-DNIEPER SAG (BASED ON SEISMIC-FACIES ANALYSIS AND GEO-SCIENCE LITERATURE REVIEW) - Nesina, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of the article is to illustrate applicability of seismic facies analysis aided by well geophysical data to mapping facial zones and reconstructing sedimentation environment during the Late-Serpukhovian period in the South-Eastern part of the researched area. Based on the data of seismic facies analysis, carried out in the Budyonivska, Nadejdinska, and Parkhomenska fields of the North-Donetsk Fault zone, there was built an enhanced seismic-facies map that accurately localizes a predictable reef structure, lagoon, shallow-water and deep-water facial zones. The facial zones have different colors that correspond to the colors of different classes used in the seismic facies analysis. On this map the boundaries of different carbonate zones between reefs, paleo-geographic zones and the lagoon anhydrites contours are marked out according to the suggestions given in the literature sources. Interpretation of the data received and published previously provided identifying patterns of biogerms occurrences within the area under research and allowed for an updated map of the Late-Serpukhovian biogerms distribution in the outermost Northern Donbas and South-Eastern part of Northern outermost Dnieper-Donetz Depression, as well as their lithological descriptions.